2004
DOI: 10.2337/diabetes.53.3.769
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Stimulated Axon Reflexes Are Diminished in Diabetic Small Fiber Neuropathies

Abstract: Axon reflex mediated flare depends on the density and the function of cutaneous C-fibers and may be impaired in diabetic neuropathy. We induced neurogenic axon reflex flare by intracutaneous electrical stimulation and analyzed size and intensity of the flare on the dorsum of the foot and ventral thigh with laser Doppler imaging (LDI). We investigated 12 diabetic subjects with small fiber neuropathies (SFNs), 5 diabetic subjects without neuropathy (NO-Ns), and 14 healthy control subjects. Five of the normal sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 45 publications
2
58
0
Order By: Relevance
“…If the CMi fibers are less affected than CM fibers, this may explain hyperalgesia observed in early stages of diabetic neuropathy on the background of elevated thresholds for painful stimuli. However, the efferent function of the CMi fibers, which has been found to be impaired in diabetic neuropathy (Kramer et al, 2004b), was not tested in this study.…”
Section: Discussionmentioning
confidence: 98%
“…If the CMi fibers are less affected than CM fibers, this may explain hyperalgesia observed in early stages of diabetic neuropathy on the background of elevated thresholds for painful stimuli. However, the efferent function of the CMi fibers, which has been found to be impaired in diabetic neuropathy (Kramer et al, 2004b), was not tested in this study.…”
Section: Discussionmentioning
confidence: 98%
“…15,33 The difference in the flare and pain response to a heat-ramp stimulus among the normal and obese subjects may be indicative of such a dissociation and, in fact, would favor a concept that the organism attempts to elicit an early protective reaction (neurogenic vasodilatation) at a temperature (441C) just below that which will become injurious to tissue. 14 Flare can be suppressed or abolished by denervation, 21,42 local anesthetics, 12,21 capsaicin-desensitization, 22,34 disease (diabetes, post-herpetic neuralgia), 21,43 and aging. 32 Under circumstances of prolonged depression of small fiber function, tissue integrity can be substantially impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, the flare response does not reach a plateau under the given experimental settings. Similarly, previous human studies also demonstrated a linear increase of flare development, which does not saturate at current intensities of 30 mA [14,15]. If current intensities are further increased, the flare area gains a maximum after 50 min of continuous stimulation at about 50-80 mA [16].…”
Section: Discussionmentioning
confidence: 87%